2017
DOI: 10.1038/srep43297
|View full text |Cite
|
Sign up to set email alerts
|

OGG1-DNA interactions facilitate NF-κB binding to DNA targets

Abstract: DNA repair protein counteracting oxidative promoter lesions may modulate gene expression. Oxidative DNA bases modified by reactive oxygen species (ROS), primarily as 7, 8-dihydro-8-oxo-2′-deoxyguanosine (8-oxoG), which is repaired by 8-oxoguanine DNA glycosylase1 (OGG1) during base excision repair (BER) pathway. Because cellular response to oxidative challenge is accompanied by DNA damage repair, we tested whether the repair by OGG1 is compatible with transcription factor binding and gene expression. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 54 publications
(68 reference statements)
7
74
1
Order By: Relevance
“…Indeed, a rapid up‐regulation of pro‐inflammatory cytokines and chemokines correlated well with an increase in both levels of 8‐oxoG and OGG1 enrichment on the TSS adjacent regulatory sequences, and intriguingly, OGG1 depletion impeded gene expression 25 . In‐depth studies revealed that OGG1's interaction with its DNA substrate facilitated DNA occupancy of sequence‐specific transcription factors on their motifs 33,39,48 . It has been proposed that to prioritize a prompt expression of ROS‐responding genes, OGG1 interacts with DNA without removal of its substrate, which, in turn, facilitates the recruitment of transcription factors and assembly of the transcriptional machinery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, a rapid up‐regulation of pro‐inflammatory cytokines and chemokines correlated well with an increase in both levels of 8‐oxoG and OGG1 enrichment on the TSS adjacent regulatory sequences, and intriguingly, OGG1 depletion impeded gene expression 25 . In‐depth studies revealed that OGG1's interaction with its DNA substrate facilitated DNA occupancy of sequence‐specific transcription factors on their motifs 33,39,48 . It has been proposed that to prioritize a prompt expression of ROS‐responding genes, OGG1 interacts with DNA without removal of its substrate, which, in turn, facilitates the recruitment of transcription factors and assembly of the transcriptional machinery.…”
Section: Discussionmentioning
confidence: 99%
“…OGG1 oxidative modification at cysteine residues is a reversible modification that can be regained after redox balance is restored 25,33,36,37 . Inactivation of OGG1 via cysteine oxidation does not interfere with genomic substrate binding, but halts its glycosylase activity 3,23,25,33‐34,39 . The vast numbers of OGG1 K249Q analyses help us to comprehend the mechanism of how oxidatively inactivated OGG1 modulates gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations